Brazilian Green Propolis as a Therapeutic Agent for the Post-surgical Treatment of Caseous Lymphadenitis in Sheep - Kalil, Mauricio Alcântara; Santos, Laerte Marlon; Barral, Thiago Doria; Rodrigues, Daniela Méria; Pereira, Neila Paula; Sá, Maria da Conceição Aquino; Umsza-Guez, Marcelo Andres; Machado, Bruna Aparecida Souza; Meyer, Roberto; Portela, Ricardo Wagner (Frontiers in Veterinary Science, 2019)
As antibiotics are ineffective when used to treat caseous lymphadenitis, the surgical excision of lesions is often required. Iodine solution (10%) is currently the choice for the post-surgical treatment; however, it may cause histotoxicity. Propolis are resinous substances composed by a mixture of different plants parts and molecules secreted by bees. As green propolis has already proven to possess antibacterial and wound healing properties, this study aimed to evaluate the use of a green propolis-based ointment as a therapeutic agent for the post-surgical treatment of caseous lymphadenitis. The caseous lesions of 28 sheep were surgically excised before dividing animals into two groups: (1) iodine-treated animals and (2) sheep treated with an ointment made with a previously characterized green propolis extract. Clinical data of animals, size of the scar area, the presence of moisture and secretion in the surgical wound, the humoral immune response against the bacterium and the susceptibility of C. pseudotuberculosis clinical isolates to the green propolis extract were analyzed. The green propolis-treated group presented complete healing of the surgical wound one week before the iodine-treated group. Additionally, animals treated with the green propolis ointment had fewer cases of wound secretion, but it was not statistically different from the iodine-treated group. No clinical signs indicating green propolis toxicity or other side effects were found, associated with a faster and more organized hair recovery by propolis use. The green propolis extract was able to inhibit the growth of 23 from the 27 C. pseudotuberculosis clinical isolates, with minimum inhibitory and minimum bactericide concentrations ranging from 01-08 mg/mL, and did not interfere with the humoral immune response against the bacterium. In addition, green propolis was able to inhibit biofilm formation by four of the C. pseudotuberculosis clinical isolates. We concluded that green propolis is a promising therapeutic agent to be used in the post-surgical treatment of caseous lymphadenitis in small ruminants due to its effects on surgical wound healing, hair recovery, inhibition of wound contamination and bacterial growth.